Total training load may explain similar strength gains and muscle hypertrophy seen in aged rats submitted to resistance training and anabolic steroids - Krause Neto, Walter; Silva, Wellington de Assis; Ciena, Adriano Polican [UNESP]; Bocalini, Danilo; Baptista Nucci, Ricardo Aparecido; Anaruma, Carlos Alberto [UNESP]; Gama, Eliane Florencio (Taylor & Francis Ltd, 2018)
This study aimed to quantify training parameters and analyze the morphological response of aged muscles submitted to resistance training and anabolic steroids. Aged Wistar rats were divided into groups: C - initial control; CF - final control; CAS - control with anabolic steroid, RT - resistance training, and RTA - resistance training with anabolic steroid. Maximum carried load, absolute and relative loads increased significantly in RT and RTA. RTA demonstrated greater relative load than RT. Average total volume, total climbing volume, relative total volume, relative total climbing volume, and mean climbing volume were similar between groups RT and RTA. For soleus, CAS, RT, and RTA enlarged cross-sectional area of type I fibers and nuclear ratio. As for type II fibers, RTA was higher than C and CF. For plantaris, RT and RTA showed significant increases in myofibers type I compared to C and CF. For type II fibers, RTA showed a significant increase compared to C and CF. Regarding the nuclear ratio, RT and RTA showed a higher ratio than C, CF, and CAS. Our results demonstrated that both RT and RTA were not different among the analyzed morphological parameters. This fact can be explained by the absence of differences found in the training variables analyzed.
Keywords: Strength training; movement; rodents